PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI HOME STAY DALAM MENINGKATKAN JUMLAH TAMU DI DESA WISATA BUDO - Lagarense, Bet El SIlisna; Tongko, Tesya Tiara; Sangari, Fonny (HOSPITALITI DAN PARIWISATA, 2025)
This study aims to analyze the use of social media as a promotional tool for homestays in increasingtourist visits to Budo Tourism Village. The research employs a descriptive qualitative approach withdata collection techniques including observation, in-depth interviews, and documentation. The mainfocus is on three social media platforms—Facebook, Instagram, and TikTok used by homestaymanagers and local tourism actors. The findings reveal that consistent and creative use of social mediacan expand promotional reach, build a positive destination image, and attract visitors, particularlyfrom the younger generation. Moreover, local community involvement in content creation enhances theauthenticity of the tourism village narrative. These findings offer practical contributions to thedevelopment of community-based digital promotion strategies in rural tourism destinations.